Persistence with prescribed antimuscarinic therapy for overactive bladder: a UK experience - Wagg, Adrian; Compion, Gerhard; Fahey, Amanda; Siddiqui, Emad (BJU international, 2012)
Study Type – Therapy (prevalence) Level of Evidence 2b What's known on the subject? and What does the study add? Persistence with long‐term medication in chronic diseases is typically low and that for overactive bladder medication is lower than average. Sub‐optimal persistence is a major challenge for the successful management of overactive bladder. Using UK prescription data, persistence was generally low across the range of antimuscarinics. Patients aged 60 years and above were more likely to persist with prescribed oral antimuscarinic drugs than younger patients (40–59 years). Solifenacin was consistently associated with the highest rate of persistence compared with the other antimuscarinics included in the study OBJECTIVES • To describe the level of persistence for patients receiving antimuscarinics for overactive bladder (OAB) over a 12‐month period based on real prescription data from the UK. • To investigate patterns of persistence with oral antimuscarinic drugs prescribed for OAB, across different age groups. PATIENTS AND METHODS • UK prescription data from a longitudinal patient database were analysed retrospectively to assess persistence with darifenacin, flavoxate, oxybutynin (extended release [ER] and immediate release [IR]), propiverine, solifenacin, tolterodine (ER/IR) and trospium. • Data were extracted from the medical records of >1 200 000 registered patients via general practice software, and anonymized prescription data were collated for all eligible patients with documented OAB (n= 4833). • Data were collected on patients who started treatment between January 2007 and December 2007 and were collected up to December 2008, to allow each patient a full 12‐month potential treatment period. Failure of persistence was declared after a gap of at least 1.5 times the length of the period of the most recent prescription. • The analysis included only patients who were new to a course of treatment (i.e. who had not been prescribed that particular treatment or dosage for at least 6 months before the study period). RESULTS • The number of patients prescribed each antimuscarinic drug varied from 23 for darifenacin to 1758 for tolterodine ER. • The longest mean persistence was reported for solifenacin (187 days versus 77−157 days for the other treatments). • At 3 months, the proportions of patients still on their original treatment were: solifenacin 58%, darifenacin 52%, tolterodine ER 47%, propiverine 47%, tolterodine IR 46%, oxybutynin ER 44%, trospium 42%, oxybutynin IR 40%, flavoxate 28%. • At 12 months, the proportions of patients still on their original treatment were: solifenacin 35%, tolterodine ER 28%, propiverine 27%, oxybutynin ER 26%, trospium 26%, tolterodine IR 24%, oxybutynin IR 22%, darifenacin 17%, flavoxate 14%. • In a sub‐analysis stratified by age, patients aged ≥60 years were more likely to persist with prescribed therapy over the 12‐month period than those aged <60 years. CONCLUSIONS • Twelve months after the initial prescription, persistence rates with pharmacotherapy in the context of OAB are generally low. • Solifenacin was associated with higher levels of persistence compared with other prescribed antimuscarinic agents. • Older people are more likely than younger patients to persist with prescribed therapy. Further studies are required to understand this finding and why patients are more likely to persist with one drug rather than another.